Undergraduate's perception of sms banking in labuan: an empirical study - Hanudin Amin; Suddin Lada; Mohd Rizal Abdul Hamid; Geoffrey H. Tanakinjal (Universiti Malaysia Sarawak, 2006)
Mobile phone for banking purpose is crucial for those who are busy with daily routine activities, especially those who are employed. In contrast, mobile phone is evolved among undergraduate students as a key social tool to connect with family members, friends and lecturers. The objective of this study is to identify the key points which relevant to the students’ perception over SMS banking by the use of a survey conducted during July – September 2005. This research used university students as the sample, namely from Labuan International Campus-Universiti Malaysia Sabah. A total of 317 students were approached which was considered as a preliminary way to observe their perception over SMS banking. Through various SPSS analyses, we discovered that 38 percent of the male respondents and 61 percent of the female respondents know what is SMS? Surprisingly, only female respondents used SMS banking with 0.95 percent, which is consistent with the study by Laforet and Li (2005) and Howcroft, Hamilton and Hewer (2002). Findings also discovered that all of the socio-demographic elements have their own level of significant. In general, it can be concluded that student’s perception were not homogeneous and an education level was insufficient to explain the SMS banking usage among the respondents.